Silencing Gene‐Engineered Injectable Hydrogel Microsphere for Regulation of Extracellular Matrix Metabolism Balance. Issue 4 (6th January 2022) - Chang, Hongze; Cai, Feng; Zhang, Yan; Jiang, Mingwei; Yang, Xiaolong; Qi, Jin; Wang, Lei; Deng, Lianfu; Cui, Wenguo; Liu, Xiaodong
Abstract: Extracellular matrix (ECM) metabolism balance is essential for maintaining tissue structure and function. However, the complex crosstalk between the ECM, resident cellular, and tissue microenvironment makes long‐term maintenance of ECM metabolism balance in an abnormal microenvironment difficult to achieve. Herein, an injectable circRNA silencing‐hydrogel microsphere (psh‐circSTC2‐lipo@MS) is constructed by grafting circSTC2 silencing genes‐loaded 1, 2‐dioleoyl‐3‐trimethylammonium‐propane/cholesterol/1, 2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine (DOTAP/Chol/DOPE) cationic liposomes on methacrylated hyaluronic acid (HAMA) microspheres via amide bonds, which could silence pathological genes in nucleus pulposus (NP) cells to regulate ECM metabolism balance in the nutrient‐restricted microenvironment, thereby inhibiting intervertebral disc (IVD) degeneration. HAMA microspheres prepared by microfluidics displayed good degradability, swellability, and injectability. And lipoplexes can be efficiently loaded and released for 27 d through chemical grafting. Cocultured under nutrient‐restricted conditions for 72 h, psh‐circSTC2‐lipo@MS significantly promotes the synthesis of ECM‐related proteins and inhibits the secretion of ECM catabolism‐related proteases in NP cells. In the rat IVD nutrient‐restricted model, local injection of psh‐circSTC2‐lipo@MS promotes ECM synthesis and restored NP tissue after 8 weeks. In summary, this study confirms that psh‐circSTC2‐lipo@MS as a safe and controllable targeted gene delivery system has great potential in regulating the ECM metabolism balance under an abnormal microenvironment. Abstract : The injectable circRNA silencing‐hydrogel microsphere capable of targeting the nutrient‐restricted microenvironment to regulate extracellular matrix metabolism balance is constructed by grafting circSTC2 silencing genes‐loaded 1, 2‐dioleoyl‐3‐trimethylammonium‐propane/cholesterol/1, 2‐dioleoyl‐sn‐glycero‐3‐phosphoethanolamine (DOTAP/Chol/DOPE) cationic liposomes on methacrylated hyaluronic acid microspheres via amide bonds, which could precisely control the release of gene vectors and effectively silence pathological genes in nucleus pulposus cells.